(untitled) (Medical Forum Monthly, 2024)
Objective: (1) To assess the perception of early initiation of insulin in type 2 diabetic mellitus in family physicians of Karachi. (2) To develop a plan to motivate the family physicians to give preference for insulin in type 2 diabetic patients. Study Design: Cross sectional study. Place and Duration of Study: This study was conducted on Family Physicians of Karachi which was divided in 18 towns from from April 2010 to December 2010. Materials and Methods: 10 family physicians were included from each town from hospitals and clinics through non probability purposive sampling technique. The data was collected through pre tested structured questionnaire have questions regarding their perception and preferences of use of insulin in type 2 diabetic patients as first treatment as compared to oral hypoglycemic therapy. Results: over all 180 family physicians were contacted out of which 133 were provide full information (response rate was 74%). Out of these 93(69.1%) were male and 40(30.1%) were female family physicians. Overall perception (63.9%) was not in favor of early initiation of insulin as monotherapy or as combined therapy. The rest (36.1%) who were of the opinion that insulin is better than oral hypoglycemic therapy, non of them were apply it clinically. Conclusion: Majority of the family physicians suggest combination of life style changes with nutritional advice and oral hypoglycemic therapy. No one suggested insulin. Only few were had the knowledge about early insulin initiation as treatment in type 2 diabetics’ mellitus. However all of them show their willingness for preferences to use insulin as first therapy in type 2 diabetes mellitus